Analisis Fluktuasi Kurs Rupiah, Inflasi, DJIM, Emas Terhadap ISSI Periode 2022-2024 - Ainur Ridwan; Nauvan Ahmad; Fitria Ayuningtias; Diah Triya Wijayanti; Bintis Ti’anatud Diniati (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This study aims to examine how the rupiah exchange rate, inflation rate, Dow Jones Islamic Market (DJIM), and gold prices affect the movement of the Indonesian Sharia Stock Index (ISSI). The method used is quantitative, with a multiple linear regression analysis approach. The analysis process begins with testing classical assumptions to ensure the feasibility of the model. The data used comes from trusted secondary sources such as Bank Indonesia (BI) and the Investing.com website, covering the period 2022 to 2024. Data processing is carried out through multiple linear regression using SPSS software. The research findings indicate that the rupiah exchange rate does not have a statistically significant effect on the ISSI, although there are indications of a positive relationship. Inflation also does not have a significant impact on the movement of the index, indicating a weak influence. In contrast, the gold price has a real and positive impact on the ISSI, while the influence of DJIM on the ISSI is not significant and shows an inconsistent correlation. Based on these results, it can be concluded that several macroeconomic variables, especially gold prices, have a significant contribution to the performance of the sharia stock market in Indonesia, while other variables show a more limited impact. For future research, it is recommended to add other variables that have the potential to influence the Islamic stock market, as well as expand the number of samples so that the results obtained are more representative and have better analytical power.